The impact of artificial intelligence on human resources management recruitment processes: a systemic review - Shamsi, Mudassir (YAYASAN MITRA PERSADA NUSANTARA, 2023)
This systematic review paper examines the implementation of artificial intelligence (AI) in Human Resources Management (HRM) recruitment processes. The study includes an analysis of academic papers, magazine articles, and highly-rated websites in related fields. By exploring the findings of this research, we aim to enhance the general understanding of AI's influence on HRM recruitment. While it is not possible to cover all topics related to this subject, the chosen research methodology is reasonable and encompasses a substantial number of articles pertaining to the core subject area. The results indicate that AI offers significant advantages in recruitment, as technology can effectively support this domain. By automating time-consuming tasks, AI frees up human resources to concentrate on more critical aspects related to performance and development. Implementing automation, cognitive insights, and cognitive engagement in the recruitment process enables systems to mimic human brain functionality, facilitating unbiased, efficient, and rapid data analysis and processing.